Pengaruh Model Pembelajaran Problem Based Instruction Terhadap Hasil Belajar IPA Siswa SMK Negeri 1 Gunungsitoli Alo’oa Tahun Pelajaran 2024/2025 - Elfianat Laoli; Kadini Kurniawati Halawa (GEN BIONIX: Jurnal Ilmiah Pendidikan Biologi, 2025)
The low science learning outcomes of students at SMK Negeri 1 Gunungsitoli Alo'oa is the main problem in this study, which is caused by the dominance of conventional teacher-centered learning models so that students are less active and motivated. This study aims to describe the average learning outcomes of students taught with the Problem Based Instruction model, describe the average learning outcomes of students taught with the conventional model, and prove the significant effect of the Problem Based Instruction model on science learning outcomes. This experimental study with a pretest-posttest group design involved samples of class XI-ADM-1 as the experimental class (25 students) and class XI-ADM-2 as the control class (26 students) selected randomly from the population. The learning outcome test instrument in the form of 5 essay questions was validated first through a logical validity test by an expert validator and a trial of the instrument to measure validity, reliability, level of difficulty, and discriminatory power. The collected data were analyzed using descriptive statistics to calculate the average learning outcomes and inferential statistics through a two-tailed t-test to test the research hypothesis. The results showed that the average learning outcome for the experimental class was 81.28, categorized as good, while the control class only achieved 73.62, categorized as adequate. The hypothesis test yielded a t-value of 3.259, which was greater than the t-value (2.011), thus Ha was accepted and Ho was rejected. These findings demonstrate that the Problem-Based Instruction model has a significant impact on improving students' science learning outcomes. Consequently, teachers are advised to adopt the Problem-Based Instruction model to create more meaningful and student-centered learning.